Le molybdene dans les sols et les plantes et son importance dans la nutrition animale en Afrique subsaharienne - Haque, I. (1987)
Summarises the role of molybdenum in soils and plants and its potential importance in livestock nutrition in sub-Saharan Africa. Discusses the functions of molybdenum in plants and animals, diagnosis including deficiency symptoms, soil testing & leaf analysis, molybdenum content of soils, factors affecting availability of molybdenum to plants, molybdenum responses, and molybdenum-copper-sulphur inter-relationships in livestock.